When Are Women More Effective Lawmakers Than Men?. Issue 2 (22nd January 2013) - Volden, Craig; Wiseman, Alan E.; Wittmer, Dana E.
<x xml:space="preserve">Abstract</x> Previous scholarship has demonstrated that female lawmakers differ from their male counterparts by engaging more fully in consensus‐building activities. We argue that this behavioral difference does not serve women equally well in all institutional settings. Contentious and partisan activities of male lawmakers may help them outperform women when in a polarized majority party. However, in the minority party, while men may choose to obstruct and delay, women continue to strive to build coalitions and bring about new policies. We find strong evidence that minority party women in the U.S. House of Representatives are better able to keep their sponsored bills alive through later stages of the legislative process than are minority party men, across the 93rd–110th Congresses (1973–2008). The opposite is true for majority party women, however, who counterbalance this lack of later success by introducing more legislation. Moreover, while the legislative style of minority party women has served them well consistently across the past four decades, majority party women have become less effective as Congress has become more polarized.